CORRELATION BETWEEN BEHAVIOR AND NURSE'S COMPLIANCE IN HAND HYGIENE FIVE MOVEMENT AT INPATIENT WARD IN SLEMAN GENERAL HOSPITAL - Iskandar, Rahayu (STIKes BTH Tasikmalaya, 2019)
Background: Washing hand is an effective way to break cross-infection chain. Hand hygiene five moment are such as : prior to contact with patient, prior to sanitation or sterilization procedure, post contact with patient's body fluid, post contact with patient, post contact with patient's surroundings.Objective: To identify The Correlation between Behavior and Nurse's Compliance in Hand Hygiene Five Movement in Inpatient Ward of Third Grade in Sleman General HospitalMethod: The type of this study was non experimental with descriptive and correlational study design. The number of samples was 60 nurses in inpatient ward of third grade in Sleman general hospital. Data analysis method was gamma correlational test.Result: The study result identified that nurses' behaviors in hand hygiene five moment in inpatient ward of third grade in Sleman general hospital were positive behaviors as many as 42 nurses (70,0%) and compliant behaviors as many as 38 nurses (63,3%). The result of bivariate test found out significant correlations between behaviors and nurses' compliance in hand hygiene five moment in inpatient ward of third grade in Sleman general hospital (p value of 0,000) and correlation test figured out r value of 0,959 which indicated strong and positive correlations.Conclusion: There were significant correlations between behaviors and nurses' compliance in hand hygiene five moment in inpatient ward of third grade in Sleman general hospital with strong and positive correlations. Keywords: Behavior, Compliance, Hand Hygiene Five Moment, Nurse.